A Critical Review of Kala in Ayurveda - Abdul Sukkur M (AYUSHDHARA, 2023)
Kala is one of the nine Karana dravya. It possesses Kriya and Guna and is Nitya and Vibhu. It is understood by the occurrence of seasons, day, night, month, year etc. It gives the knowledge of past, present and future events. Kala plays its role from the birth to the death throughout the lifetime of an individual. The flowering, ripening, shedding of leaves in plants and other natural events are influenced by Kala. The Bhishak is referred as Kalavith. Methods: Kala or Time factor is explained in detail in Ayurveda literature from which important portions has been taken related with the study. Results: Available references on the study of Kala have been collected from the literature and information has been laid down to substantiate its importance in healthy and ill persons. Discussion and Conclusion: Kala is considered as a significant factor in the maintenance of healthy life in individuals and for an ill person the same Kala is understood as one of three causes for the disease condition. Time is continuously undergoing changes and a non-controlling entity because of which it is related to God.